The way storytellers communicate to influence the audience's reactions in the Kumpul Dongeng Surabaya Community - Nabila Mustikaning Tyas (LPPM Stikosa-AWS, 2023)
Realizing that not everyone can tell stories well and engagingly, a researcher is interested in investigating the communication patterns of storytellers in creating audience responses in the